PREVALÊNCIA E FATORES ASSOCIADOS A GESTAÇÃO NÃO PLANEJADA DAS PUÉRPERAS ATENDIDAS EM HOSPITAL PÚBLICO NA CIDADE DE SANTA MARIA, RS. - Flores, Bruno Bohrer (2022)
Unplanned pregnancy is every gestation that was not previously planned by the couple or at least the mother. In Brazil, unintended pregnancy is a public health issue and an important indicator of flaws in the control of the reproductive process, increasing the risk of maternal morbidity and mortality and causing an impact over the personal, family and socioeconomic well being. Objectives: To evaluate the prevalence and associated factors to unplanned pregnancy in a public hospital in Santa Maria, RS. Methodology: It is a qualitative and descriptive research, with a cross-sectional design, carried out at the puerperium outpatient clinic of Hospital Casa de Saúde, between january and april of 2022. Results: Unplanned pregnancy represented 70% of the one hundred cases. A birth control method was used by 67% of those patients, of which 32,9% reported irregular use of it, 20% stopped use due to adverse effetcs and approximately 21,4% reported abandoning it for not believing they would get pregnant. Younger patients and in short term relationships were in higher risk of unwanted pregnancy. Conclusion: Unplanned pregnancy is a strong reality in our community. Even though patients have access to medical evaluation and contraceptive methods, it is challenging for them to keep adequate use of it. Younger patients and in short term relationships were in higher risk of unwanted pregnancy. We emphazise the importance of creating new strategies to the patients in reproductive planning, aiming to lower the rated of unintended pregnancies.